Psikoedukasi Sebagai Upaya Meningkatkan Pemahaman Kesiapan Perkawinan Bagi Remaja - Martha Kurnia Asih; Shinta Pratiwi; Retno Ristiasih Utami; Kimmy Katkar (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims to increase the youth's understanding of the importance of resilience, including physical, psychological, and financial readiness. This service was implemented in psychoeducation with the target students in Kesatrian 2 Semarang Senior High School. This service instrument used a questionnaire and was analyzed by pretest and post-test. Based on the analysis using the Paired Sample T-Test, it was concluded that there was an increase of 14.31 with a mean pretest difference score of 72.54 and 86.81 post-test. It showed an increased understanding of adolescent marriage readiness after being given psychoeducation. The activities benefit adolescents with advanced knowledge of marriage readiness, including physical, psychological, and financial readiness.